Variegated clonality and rapid emergence of new molecular lesions in xenografts of acute lymphoblastic leukemia are associated with drug resistance - Nowak, Daniel; Nowak, Verena; Jann, Johann-Christoph; Hofmann, Wolf-Karsten (Experimental hematology, 2015)
The use of genome-wide copy-number analysis and massive parallel sequencing has revolutionized the understanding of the clonal architecture of pediatric acute lymphoblastic leukemia (ALL) by demonstrating that this disease is composed of highly variable clonal ancestries following the rules of Darwinian selection. The current study aimed to analyze the molecular composition of childhood ALL biopsies and patient-derived xenografts with particular emphasis on mechanisms associated with acquired chemoresistance. Genomic DNA from seven primary pediatric ALL patient samples, 29 serially passaged xenografts, and six in vivo selected chemoresistant xenografts were analyzed with 250K single-nucleotide polymorphism arrays. Copy-number analysis of non-drug-selected xenografts confirmed a highly variable molecular pattern of variegated subclones. Whereas primary patient samples from initial diagnosis displayed a mean of 5.7 copy-number alterations per sample, serially passaged xenografts contained a mean of 8.2 and chemoresistant xenografts a mean of 10.5 copy-number alterations per sample, respectively. Resistance to cytarabine was explained by a new homozygous deletion of the DCK gene, whereas methotrexate resistance was associated with monoallelic deletion of FPGS and mutation of the remaining allele. This study demonstrates that selecting for chemoresistance in xenografted human ALL cells can reveal novel mechanisms associated with drug resistance.